PEMBERDAYAAN KELOMPOK PEMBUDIDAYA KERAPU MELALUI TRANSFER TEKNOLOGI PROBIOTIK EM4 DAN ALAT MONITORING KUALITAS AIR DIGITAL DI KAMPUNG MADONG - Daniel Sinaga; Fitria Ulfah; Ronia Tambunan (Jurnal Abdi Insani, 2026)
This community service program aimed to enhance production capacity and fish health management of grouper (Epinephelus spp.) culture in the “Maju Mandiri” farmer group in Kampung Madong, Tanjungpinang City. The main problems faced by the partner included high fish mortality, low productivity, limited adoption of modern aquaculture technologies, and inadequate water quality monitoring systems. The implemented solutions comprised training on seed selection, application of fish health management based on EM4 probiotics, and the use of digital water quality monitoring devices. The program was conducted through socialization, technical training, technology implementation, and intensive participatory assistance involving lecturers, students, and community partners. The results showed an increase in grouper survival rate up to approximately 85%, a reduction in disease symptoms, improvement in the aquaculture environment quality, and enhanced production and efficiency of fish health management. The program also strengthened institutional capacity of the partner group and promoted active student involvement in technology transfer. Consistent application of the introduced technologies is essential to ensure program sustainability in supporting food security and strengthening the coastal community economy.